Case reportsSynchronous primary lung cancers in a 51-year-old woman – a case report and literature review - Rogoziński, Paweł; Kucharzewski, Marek; Bruliński, Krzysztof (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Synchronous primary lung cancers are two primary lung cancers diagnosed at the same time in one patient. The authors report the case of a 51-year-old woman who incidentally discovered tumors in both lungs. The patient underwent cytological diagnosis and PET-CT. There was no radiological evidence of lymph node involvement. On the left side, segmentectomy I was performed (large cell carcinoma), on the right side, upper lobectomy was performed (two foci of adenocarcinoma), and lymphadenectomy was performed on both sides – there was no histopathological evidence of mediastinal lymph node involvement. In view of the obtained results, the patient was diagnosed with synchronous primary lung cancers. Subsequently, the authors conducted a systematic review of the literature on synchronous primary lung cancers published in the last decade. They point out that the classification of synchronous primary lung cancers still remains an open issue, as it is not taken into consideration by the current TNM classification (7th edition).